Axially-symmetric quasi-neutral charged dust distributions in general relativity - Ram S. (My University, 2025)
A solution of Einstein-Maxwell equations representing a distribution of equal and opposite charges moving in circles in opposite directions around the z-axis is obtained. In a particular case the solution reduces to the special case of Levi-Civita metric for a line-mass placed along the z-axis. The asymptotic behaviour of the solution is also discussed. © 1985 D. Reidel Publishing Company.